2020
DOI: 10.3389/fonc.2020.593102
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Estimation of Glioma IDH1 Mutation and VEGF Expression by Histogram Analysis of Dynamic Contrast-Enhanced MRI

Abstract: ObjectivesTo investigate whether glioma isocitrate dehydrogenase (IDH) 1 mutation and vascular endothelial growth factor (VEGF) expression can be estimated by histogram analysis of dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI).MethodsChinese Glioma Genome Atlas (CGGA) database was wined for differential expression of VEGF in gliomas with different IDH genotypes. The VEGF expression and IDH1 genotypes of 56 glioma samples in our hospital were assessed by immunohistochemistry. Preoperative DCE-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Therefore, the observed relationship between Ktrans (Quantile 90) and Ktrans (Quantile 50) and VEGF expression is reasonable. The findings reported in this study are consistent with those of previous reports in that VEGF and Ktrans have significantly positive associations in gliomas [ 24 , 25 ]. Furthermore, this study indicated that VEGF expression in diffuse-type AGC was significantly higher than that in intestinal-type AGC.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the observed relationship between Ktrans (Quantile 90) and Ktrans (Quantile 50) and VEGF expression is reasonable. The findings reported in this study are consistent with those of previous reports in that VEGF and Ktrans have significantly positive associations in gliomas [ 24 , 25 ]. Furthermore, this study indicated that VEGF expression in diffuse-type AGC was significantly higher than that in intestinal-type AGC.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, studies revealed that DCE‐driven parameters were able to predict some of the molecular characteristics used recently for the classification of glioma tumors, including IDH and MGMT methylation. Hu et al reported statistically significant differences in histogram parameters of K trans and V e between IDH‐mutated and IDH‐wild‐type glioma 53 . Furthermore, Zhang et al found that glioblastoma with MGMT methylation showed significantly higher K trans , indicating that MGMT methylation may be involved in glioma‐associated angiogenesis characterized by high endothelial permeability vasculatures 48 .…”
Section: Resultsmentioning
confidence: 99%
“…Transforming growth factor-β and hypoxic signals are increased in IDH wild-type low-grade gliomas, and neovascularization in IDH-mutated and wild-type tumors has different molecular features [ 14 ]. Expression of VEGF, which is involved in neovascularization, is significantly lower in IDH-mutated gliomas [ 15 ]. These reports suggest that IDH wild-type gliomas have more aggressive neovascularization, which can lead to poorer outcomes.…”
Section: Discussionmentioning
confidence: 99%